Dampak Penggunaan Media Sosial terhadap Kepercayaan Diri dalam Hal Citra Tubuh pada Generasi Z di Kota Cimahi - Ocha Febriyanti; Andinna Salsabela; Anggi Fatma Triyani (Jurnal Hukum, Administrasi Publik dan Negara, 2024)
This research aims to explore the impact of social media use on self-confidence related to body image in Generation Z in Cimahi City. This study uses a qualitative approach by conducting in-depth interviews with a number of participants who represent a variety of experiences and perspectives regarding this topic. The research results show that social media has a significant role in shaping individuals' self-perception and body image, both positively and negatively. These findings provide insight into how social media influences young people's self-confidence in the context of their local culture and environment.